Faculty Members' Perceptions of Quality Assurance and Accreditation in Afghanistan - Sayed Ahmad Javid Mussawy; Gretchen B Rossman (Laureate Education Inc, 2018)
Abstract This study investigated faculty members' perceptions of quality assurance and accreditation (QAA) in Afghanistan. The study aimed to examine how familiar faculty members were with QAA policy, quality concepts, QAA processes, and whether QAA process has improved the status quo. Through a sequential exploratory mixed methods design, the investigators interviewed seven faculty members at four universities, and subsequently conducted a self-administered survey questionnaire at six universities (two public and four private). A response rate of 54 percent (N = 42) was obtained from the survey. The study findings suggest that faculty members had mixed impressions about QAA implementation. For instance, an overall sum of mean scores shows that faculty members have a positive view about QAA processes M = 3.5 (SD = .75), however, interview participants were less satisfied with QAA outcome. Lastly, implications are made that a successful implementation of QAA processes in Afghanistan is contingent on: 1) establishment of a quality culture wherein universities own the processes and outcomes, and 2) engagement of key stakeholders including faculty, staff, and administrators to internalize QAA processes to improve the status quo. Keywords: higher education quality; quality assurance; accreditation; higher education in Afghanistan